Arenosol Epieuric and Haplic Cambisol show a similar level of resilience of microbial communities when irrigated with treated wastewater in a temperate climate - Chroňáková, Alica; Choma, Michal; Kotrbová, Lucie; Lara, Ana Catalina; Villeneuve, Clara; Calvillo-Medina, Rosa Paulina; Jílková, Veronika; Kodešová, Radka (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2024)
The reuse of treated wastewater for irrigation purposes in agriculture is a common but controversial means of saving freshwater and providing plants with nutrients. It often leads to a change in physico-chemical properties and the introduction of uncontrolled amounts of pollutants into the soil. As a result, the structures and functions of soil microbial communities can change to an unknown extent. The aim of this study was to investigate the effect of treated wastewater on the abundance, diversity, and composition of bacteria, fungi, and ammonia oxidizers in two arable soils, the Arenosol and Cambisol. The raised soil beds were regularly irrigated with tap water (W) or effluent (E) and used for a vegetable crop rotation. Changes in soil chemical properties, nutrient content, abundance and composition of ammonia oxidizers, bacteria, and fungi were evaluated after 0, 54, 115, and 152 days. Irrigation with effluent led to an increase in salinity in both soils, while dissolved organic carbon (C) content, nitrate concentration and oxidizable C content showed soil-dependent response. Neither soil bacteria nor ammonia oxidizers were affected by the effluent in any soil, but time-dependent differences between fungal communities between W- and E-irrigated soils were observed. Our results indicate microbial taxa or guilds that were more sensitive to wastewater irrigation (Apiotrichum) and those that can thrive in altered soil conditions (Plectosphaera and Pseudopithomyces). However, this effect was overshadowed by changes caused by the crop rotation, indicating high quality of treated wastewater used for irrigation. [Display omitted] •Treated wastewater increased soil salinity; other soil parameters remained stable.•The effect of treated wastewater was generally lower than seasonal variability.•Bacterial communities including ammonia oxidizers showed a high level of resilience.•Apiotrichum as the most sensitive taxon can serve as an indicator for treated wastewater.•Plectosphaera and Pseudopithomyces thrived in altered soil conditions.